2019
DOI: 10.1002/cctc.201901062
|View full text |Cite
|
Sign up to set email alerts
|

Bimetallic Fe‐Promoted Catalyst for CO‐Free Hydrogen Production in High‐Temperature‐Methanol Steam Reforming

Abstract: The current work investigates various bimetallic catalysts supported on Al2O3−Zn−ZrO2 to determine a catalyst with minimal CO selectivity at high temperature for methanol steam reforming. Characterization tools employed in this study include temperature programmed reduction, X‐ray diffraction, X‐ray photoelectron spectroscopy and transmission electron microscopy. Activity testing for all the catalysts synthesized were performed in the temperature range of 150 to 500 °C. Bimetallic catalyst with addition of Fe … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 32 publications
(7 citation statements)
references
References 64 publications
0
7
0
Order By: Relevance
“…DRIFTs analysis showed that the presence of Fe 2 O 3 as the surface species on the catalyst was responsible for the conversion of generated CO to CO 2 . 78,79…”
Section: Srmmentioning
confidence: 99%
See 1 more Smart Citation
“…DRIFTs analysis showed that the presence of Fe 2 O 3 as the surface species on the catalyst was responsible for the conversion of generated CO to CO 2 . 78,79…”
Section: Srmmentioning
confidence: 99%
“…When copper content is higher than 75%, the selectivity for CO becomes almost zero. DRIFTs analysis showed that the presence of Fe 2 O 3 as the surface species on the catalyst was responsible for the conversion of generated CO to CO 2 . , …”
Section: Introductionmentioning
confidence: 98%
“…Hence, the addition of lanthanum improves metallic dispersion and has positive effects on active phase support interaction, sintering resistance, and carbon deposition [37] . Similarly, Fe improves the WGS reaction performance and hence helps in reducing the CO selectivity [38] . Therefore, in the current work, a novel La and Fe promoted Ni based catalyst is synthesized for steam reforming of methane targeting membrane reformer application.…”
Section: Introductionmentioning
confidence: 99%
“…[37] Similarly, Fe improves the WGS reaction performance and hence helps in reducing the CO selectivity. [38] Therefore, in the current work, a novel La and Fe promoted Ni based catalyst is synthesized for steam reforming of methane targeting membrane reformer application. The study uses commercial alumina and ceria as support.…”
Section: Introductionmentioning
confidence: 99%
“…PEMFCs have little tolerance for CO; even if the operating temperature of PEMFCs is increased, the tolerance of Heat Temperature‐PEMFCs (HT‐PEMFCs) to CO is only 3.0% 9 . Some studies suggest that CO is a potent poison, and it will have a destructive impact on the performance of catalysts over time 10 . Therefore, it is necessary to inhibit the production of CO in MSR reactions.…”
Section: Introductionmentioning
confidence: 99%